2021
DOI: 10.1007/s40820-021-00738-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Interface Engineering for Electrocatalytic CO2 Reduction Reaction

Abstract: Electrocatalytic CO2 reduction reaction (CO2RR) can store and transform the intermittent renewable energy in the form of chemical energy for industrial production of chemicals and fuels, which can dramatically reduce CO2 emission and contribute to carbon-neutral cycle. Efficient electrocatalytic reduction of chemically inert CO2 is challenging from thermodynamic and kinetic points of view. Therefore, low-cost, highly efficient, and readily available electrocatalysts have been the focus for promoting the conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 265 publications
(389 reference statements)
0
60
0
Order By: Relevance
“…However, up to date, no studies have reported photocatalytic CRR over isotype heterojunctions. Uncovering the detailed reaction mechanism can provide new insights into modulating the catalytic behavior by junction engineering in photocatalytic CRR materials [31][32][33][34][35]. Particularly, it is well known that enhanced photogenerated carrier dynamics enables higher performances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, up to date, no studies have reported photocatalytic CRR over isotype heterojunctions. Uncovering the detailed reaction mechanism can provide new insights into modulating the catalytic behavior by junction engineering in photocatalytic CRR materials [31][32][33][34][35]. Particularly, it is well known that enhanced photogenerated carrier dynamics enables higher performances.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, it is well known that enhanced photogenerated carrier dynamics enables higher performances. However, a long-standing question in photocatalysis is that how such enhancement actually contributes to the overall reaction kinetics [31,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The interface is formed by the complex bonding or synergistic effect of different components 41 . It can regulate the electronic structure, electron transfer, mass transport, and the binding energy of reaction intermediates to accelerate the electrochemical CO 2 RR performances 42,43 . Thus, the surface and interface chemistry of MFEs can improve the activity and selectivity of CO 2 RR from the view of thermodynamics and kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 44 focused on the interfacial effect of supported catalysts in CO 2 RR. Hu et al 43 reviewed recent progress of interface engineering in turning the CO 2 RR performance by electronic and/or structural modulation, involving the metal–metal, metal–metal oxide, metal‐nonmetal, metal oxide‐metal oxide, and so on. They also discussed that the electronic and/or structural modulation could adjust electron, proton, mass, intermediates, and local reactant concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The j formate of In@NC displays a gradual upward trend as the applied potential increases, indicating that the metallic In can promote the production of formate during the ECR process. 34 Strikingly, the In-SACs possess much higher j formate than In@NC. Unlike the linear increase of the total current density with the applied potential (Fig.…”
mentioning
confidence: 99%